Effect of premodulated interferential current versus diadynamic current on the management of lateral elbow tendinopathy - Abdelatief Emad Eldin Mohamed; Almaboud Bassam Ahmed Nabil Abd (Sciendo, 2023)
Study aim: To compare the effect of premodulated interferential current (PREMOD IFC) and diadynamic current (DD) with exercise training on the management of lateral elbow tendinopathy (LET).